Handbook on the International Political Economy of Gender 2018
DOI: 10.4337/9781783478842.00005
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: situating gender scholarship in IPE

Abstract: This collection marks an effort to showcase the wide-ranging scholarship that has come to constitute the study of gender and International Political Economy (IPE). The publication of a handbook of this nature marks an important point in the development of the field of gender and IPE. In recent years, feminist scholars working in and around IPE have made some important efforts to raise the status and standing of genderfocused work. This has resulted in a number of journal special issues (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similar to themes such as gender or race, it is not sufficient to simply 'incorporate' environmental factors into existing research, but to develop perspectives and research programmes centring around climate breakdown. As Elias and Roberts (2018) argue that gender scholarship in IPE is more than simply analysing how globalisation impacts women, an IPE perspective on climate breakdown should go beyond merely analysing how the environment is affected by global political and economic processes. The benchmark for successful centring of climate breakdown into IPE consist in our view in the establishment of research programmes that are both, systematic and concrete.…”
Section: Critical Ipe In the Age Of Climate Breakdownmentioning
confidence: 99%
“…Similar to themes such as gender or race, it is not sufficient to simply 'incorporate' environmental factors into existing research, but to develop perspectives and research programmes centring around climate breakdown. As Elias and Roberts (2018) argue that gender scholarship in IPE is more than simply analysing how globalisation impacts women, an IPE perspective on climate breakdown should go beyond merely analysing how the environment is affected by global political and economic processes. The benchmark for successful centring of climate breakdown into IPE consist in our view in the establishment of research programmes that are both, systematic and concrete.…”
Section: Critical Ipe In the Age Of Climate Breakdownmentioning
confidence: 99%
“…Previous literature has found that women's place in the IPE is defined by a patriarchal structure that exhibits informal barriers such as gender bias, discrimination, segregation, heteronormative behaviours, and unpaid or informal labour (Stromquist, 1991;Ellerby, 2017;Elias and Roberts, 2018). These informal barriers keep them from succeeding in the same space and at the same levels as men.…”
Section: Patriarchal Economic Structurementioning
confidence: 99%
“…Without the same opportunities as men to enter the workforce, women frequently face a low level of economic autonomy and empowerment inside the state. When women do enter this space, they take on low-paid, labour-intensive, and service-oriented jobs (Elias and Roberts, 2018). This economic inequality between the genders links back to gender norms and societal expectations of suitable work and pay.…”
Section: Patriarchal Economic Structurementioning
confidence: 99%
“…In particular, work that seeks to reconsider how empirical schisms have emerged between understandings of security and economy, that limit the possibilities for more integrated analyses. 2 From our -outsiders -perspective, IPS appears as a diverse and open-ended field of study that certainly shares significant commonalities, overlaps and intellectual histories with many strands of IPE scholarship. 3 Even as IPS scholarship has become ever more attuned to a concern with the materiality of international politics -revealed in its border fences, garbage flows and mass graves 4,5,6 -there exists disquiet about the extent to which such a focus displays a relative inattention to proliferating markets, economic transformations and material inequalities.…”
mentioning
confidence: 99%